2007
DOI: 10.1111/j.1744-1617.2007.00143.x
|View full text |Cite
|
Sign up to set email alerts
|

Initial Development of a Psychological Model for Judicial Decision Making in Continuing Restraining Orders

Abstract: Probate and family court judges are increasingly called upon to make rapid decisions regarding the continuance of restraining orders. These decisions are often made without the benefit of adequate background information or an awareness of which psychological and behavioral factors are most relevant. This action-oriented research project develops a model that brings psychosocial factors to consideration for judges making decisions regarding the continuance of restraining orders. While further evaluation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…DVPOs are the most widely used IPV-related legal intervention in the United States (Ballou et al, 2007;DeJong & Burgess-Proctor, 2006;Dugan, 2003;Jordan, 2004;Logan, Shannon, Walker, & Faragher, 2006). More than a million DVPOs are issued every year, and data from the Massachusetts BRFSS indicate that among women 18 to 59 who reported experiencing IPV during the preceding 5 years, 39% had police contact, and 34% had obtained a protective order (Hathaway et al, 2000).…”
Section: Intimate Partner Violencementioning
confidence: 99%
See 1 more Smart Citation
“…DVPOs are the most widely used IPV-related legal intervention in the United States (Ballou et al, 2007;DeJong & Burgess-Proctor, 2006;Dugan, 2003;Jordan, 2004;Logan, Shannon, Walker, & Faragher, 2006). More than a million DVPOs are issued every year, and data from the Massachusetts BRFSS indicate that among women 18 to 59 who reported experiencing IPV during the preceding 5 years, 39% had police contact, and 34% had obtained a protective order (Hathaway et al, 2000).…”
Section: Intimate Partner Violencementioning
confidence: 99%
“…The decision to seek a protection order is initiated by the victim, and she is able to request that a variety of provisions be included in the order, giving her more control over the intervention than is the case with criminal prosecution. DVPOs entail fewer legal barriers than criminal prosecution and require a lower evidentiary standard of proof, which is particularly important given that IPV often takes place in the home, away from public scrutiny (Ballou et al, 2007;DeJong & Burgess-Proctor, 2006;Dugan, 2003;Kanuha & Ross, 2004;Lewis, Dobash, Dobash, & Cavanaugh, 2001;Logan et al, 2006;Logan, Shannon, & Walker, 2005;Malecha et al, 2003;Meloy, Cowett, Parker, Hofland, & Friedland, 1997;National Council of Juvenile and Family Court Judges, 2005;Wan, 2000). Preliminary hearings are usually held immediately, providing victims with timely protection, and the civil procedures involved are less time consuming than those entailed in criminal trials.…”
Section: Intimate Partner Violencementioning
confidence: 99%
“…In response to this violence, many victims turn to legal measures to protect themselves and their children. Civil protection orders, often referred to as restraining orders, are among the most widely used legal interventions for IPV (Ballou et al 2007; DeJong & Burgess‐Proctor 2006; Jordan 2004; Logan et al 2005b). US courts issue roughly 1 million civil protection orders every year (Fleury‐Steiner et al 2016).…”
mentioning
confidence: 99%
“…As indicated by responses in interviews, some judges seemed unfamiliar with common effects of trauma exhibited by IPV survivors. Previous research has shown that IPV survivors’ affect may cause judges to make decisions based on insufficient or misleading information (Ballou et al, 2007). For example, some judges discussed the amount of time passed since the violent incident on record to be a major factor in their decision-making process; however, persons who experience abuse are often subjected to chronic, long-term acts of violence and may have been too traumatized or too fearful to come forward immediately after an abusive incident.…”
Section: Discussionmentioning
confidence: 99%